Oxidative Stress—the Key Mechanism of Diabetic Peripheral Neuropathy - Zhang, MD, Taojing; Gong, MD, Yanbing; Zhou, MD, Hui; Xie, MM, Peifeng; Guan, MM, Song; Yi, MM, Wenming (North American Journal of Medicine and Science, 2013)
In China, there are more than one hundred million people with diabetes, among which 60% have diabetic peripheral neuropathy (DPN). However, because of the unclear mechanism there is no effective drug for DPN. In this review, we present the current oxidative stress hypothesis and the relationship between the classical and accepted DPN mechanism pathways and oxidative stress. Furthermore, the two signal pathways are important for oxidative stress. Recent studies have focused on the intracellular oxidative stress, especially from mitochondria. As the foremost energy metabolic organelle mitochondria is affected in many aspects after hyperglycemia. Better understanding of the relationship between DPN and oxidative stress may provide insights into new drug therapies. [N A J Med Sci. 2013;6(2):87-90. DOI: 10.7156/najms.2013.0602087]